The Correlation of Asymptomatic Hyperuricemia Patients and their Comorbidities at Sint Carolus Hospital - Cindy Oey; Emon Winardi Danudirgo; Bettia Bermawi (Indonesian Journal of Rheumatology, 2020)
Background Gout is a progressive disease due to Mono Sodium Urate (MSU) crystal deposition at joints, kidney, and other connective tissue, caused by chronic hyperuricemia.1 In both developed and developing countries, there were increasing prevalence and incidence of gout in recent decades. Patients with hyperuricaemia are at risk of developing a variety of comorbidities, such as hypertension, chronic kidney disease, cardiovascular diseases, and metabolic syndromes.2 Method Total 303 patients with asymptomatic hyperuricemia from Internal Medicine, Neurology, and Cardiology departments of Sint Carolus Hospital Jakarta admitted in January until December 2019 were recorded and analyzed for its comorbidities. Result The number of asymptomatic hyperuricemia patients was higher that gouty arthritis, mostly men, middle-aged, with the median level of uric acid 7.7 mg/dl. The most frequent comorbidity found in this study was hypertension. Majority of the population has 2 comorbidities, higher UA level (>8 mg/dl) had more comorbidities compared to lower UA level (â‰¥6.8-8 mg/dl), 4 vs 2 comorbidities respectively. Fisher exact test shown that higher UA level has a significant relatioship with the presence of hypertension, dislipidemia, cardiovascular disease, chronic renal failure, stroke, and diabetes mellitus (p <0.05). Conclusion Hyperuricemia can be easily detected in routine medical care and might be a potential biomarker independently predicting the development of hypertension, dislipidemia, cardiovascular disease, chronic renal failure, stroke, and diabetes. Thus we suggested that every person with hyperuricemia should be systematically screened for associated comorbidities, which should be addressed as an integral part of the management of hyperuricemia. Keywords : asymptomatic hyperuricemia, comorbidities, sint carolus hospital.